Case report: A rare case of malignant solitary fibrous tumor in an adult with an epithelioid pattern in the occipital region - Huang, Ke; Liu, Wen-wen; Chen, Xiu-wen; Hao, Yin-hua; Luo, Sen-yuan; Yuan, Ling-ling; Huang, Yu-gang; Tang, Xian-bin (Frontiers in Oncology, 2024)
We illustrated a rare case of malignant solitary fibrous tumor (MSFT) with epithelioid morphology in the occipital region of a 59-year-old female, in which a rare NAB2ex7-STAT6 exon15/16 double fusion subtype was detected by the Next-generation sequencing (NGS) and STAT6 immunohistochemistry (IHC) was diffusely and strongly positively expressed, without recurrence after 20 months of postoperative follow-up. The morphological and molecular genetic aspects and the differential diagnosis are described, and the relevant literature was assessed in order to broaden our understanding and diagnostic capability of this malignancy.